2016
DOI: 10.1371/journal.pone.0159051
|View full text |Cite
|
Sign up to set email alerts
|

PA6 Stromal Cell Co-Culture Enhances SH-SY5Y and VSC4.1 Neuroblastoma Differentiation to Mature Phenotypes

Abstract: Neuroblastoma cell lines such as SH-SY5Y have been used for modelling neurodegenerative diseases and for studying basic mechanisms in neuroscience. Since neuroblastoma cells proliferate and generally do not express markers of mature or functional neurons, we exploited a co-culture system with the stromal cell line PA6 to better induce differentiation to a more physiologically relevant status. We found that co-culture of the neuroblastoma cell lines in the presence of neural inducers such retinoic acid was able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Being a dopaminergic neuronal cell, human neuroblastoma cells (SHSY5Y) are becoming more popular as a model for neuroscience research particularly neurodegenerative diseases including but not limited to Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), Amyotrophic lateral sclerosis (ALS) and Multiple sclerosis (MS) [ 37 39 ]. The cells develop neuronal properties such as neural extension and expression of certain neuron specific markers upon regular incubation with 10 μM all-trans retinoic acid (RA) or other differentiation inducers for appropriate period [ 40 , 41 ]. However, study have shown that differentiation process of SHSY5Y to full neuronal cells lower their susceptibility to cytotoxic effect of various compounds [ 42 ], thereby enhancing their stability compared to undifferentiated version of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Being a dopaminergic neuronal cell, human neuroblastoma cells (SHSY5Y) are becoming more popular as a model for neuroscience research particularly neurodegenerative diseases including but not limited to Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), Amyotrophic lateral sclerosis (ALS) and Multiple sclerosis (MS) [ 37 39 ]. The cells develop neuronal properties such as neural extension and expression of certain neuron specific markers upon regular incubation with 10 μM all-trans retinoic acid (RA) or other differentiation inducers for appropriate period [ 40 , 41 ]. However, study have shown that differentiation process of SHSY5Y to full neuronal cells lower their susceptibility to cytotoxic effect of various compounds [ 42 ], thereby enhancing their stability compared to undifferentiated version of cells.…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells are a subclone of a human neuroblastoma cell line and exhibit a neuroblast-like phenotype. These cells express a marker of stem cell characteristics ( 46 ), namely, nestin, under undifferentiated conditions and differentiate into neurons in the presence of retinoic acid ( 47 ), which allows investigations on neuronal differentiation via the addition of drugs or molecules. In our study, we could not prove the differentiation of SH-SY5Y cells to a mature neuronal phenotype with neurite outgrowth when treated with angiogenin at the tested doses since neither circuit or neurite length were enhanced in the presence of angiogenin.…”
Section: Discussionmentioning
confidence: 99%
“…As positive controls, we used ATRA at the two concentrations of 1.16 × 10 −9 M (i.e., comparable to that conjugated to the polymer) as well as of 1 × 10 −5 M, which is the standard condition to promote neuroblastoma cells differentiation [ 54 , 62 , 63 ]. Additionally, control samples of PVA@Rhod (2.4 × 10 −7 M) and PVA@Rhod +RA (i.e., the physical mixture of the polymer and ATRA, at the final PVA@Rhod concentration of 2.4 × 10 −7 M, while ATRA was added at the two concentrations of 1.16 × 10 −9 M and 1 × 10 −5 M, respectively) were used.…”
Section: Methodsmentioning
confidence: 99%
“…These experiments allowed us to assess the neurite outgrowth of the samples over time and scrutinise the neurite morphology by confocal laser microscopy using a fluorescent structural marker, namely, actin green, which has a high affinity for the cytoskeletal actin protein. Compared to the standard condition that is already used to promote the formation of neuron-like cells [ 54 ], the biological response to PVA@RhodFR revealed the ability of the new polymeric conjugate to induce neuroblastoma cells differentiation, even for a short incubation time and low ATRA concentration, highlighting the promising potential of this new compound in brain cancer treatment. In addition to developing ATRA–polymer conjugates, the proposed approach was also exploited to obtain water-soluble conjugates that are useful in theranostics by covalently linking different on-demand drugs and targeting and tracking agents to the PVA chain.…”
Section: Introductionmentioning
confidence: 99%